Effect of Ethyl Methane Sulfonate on Bulbil Explant Growth and In Vitro Shoot Formation in Porang (Amorphophallus muelleri Blume) - Febriyanti, Vera; Waluyo, Budi; Harijati, Nunung; Martasari, Chaireni; Widoretno, Wahyu (The Journal of Experimental Life Science, 2024)
Porang is one of the plant commodities with high economic value due to its high glucomannan content in the tubers. Currently, the global demand for porang tubers continues to rise, but domestic production has not yet met this demand due to the limited supply of superior porang seeds. Mutation breeding with Ethyl Methane Sulfonate (EMS) can be one of the alternative methods for developing superior porang to enhance tuber production. This study aims to determine the response of porang bulbil explants to EMS mutagen treatment in vitro. The research used a Randomized Complete Block Design consisting of six EMS concentrations (0, 0.02, 0.04, 0.06, 0.08, and 0.1%). The research stages included pre-culture of bulbil explants on MS + BAP 3 mg.L-1 + NAA 0.1 mg.L-1 for two weeks in dark conditions and EMS mutagen treatment on bulbil cultures for four weeks. The results showed that adding EMS mutagen to the medium for four weeks caused the explants browning, inhibited shoots forming, and decreased the fresh weight and growth index. The higher the EMS concentration in the medium, the increased percentage of browning explants and reduced explant growth and shoot formation. The EMS concentration (≥0.06%) inhibited explant growth and shoot formation. While EMS concentration (0.02-0.04%) increased explant growth, shoot formation was not significantly different from control, even though there was an increase. Up to four weeks of culture, there was no explant death, so LD50 is not yet known. The LD50 EMS can also be calculated by explant browning and shoot proliferation. Based on explant browning and shoot proliferation, the LD50 EMS in porang bulbil explants was 0.07% and 0.09%. The EMS concentration and length of culture age need to be increased to obtain an LD50 survival rate. Keywords: Amorphophallus muelleri Blume, bulbil, EMS, In Vitro mutagenesis.